Persentase Tutupan Terumbu Karang di Perairan Pasir Putih Kabupaten Manokwari - Adi Ivandi Thovyan; Vera Sabariah; Dedi Parenden (Jurnal Sumberdaya Akuatik Indopasifik, 2017)
This research was done on October-November 2014 at Pasir Putih coastal area of Manokwari Regency and located at Air Salobar beach. The research aimed to know percent cover of coral reef, physical and chemical water quality, also the correlation of water quality to coral reef percent cover at southern west part of Pasir Putih coast in Manokwari. The method used in this study was Point Intercept Transect (PIT) at the depth of 3 m (Transect I), 7 m (Transect II) dan 10 m (Transect III) to determine coral reef. Results showed that percent cover of coral reef on Transect I was 91%, Transect II 78% amd Transect III 54%. Coral reef condition in Pasir Putih coast was in good to very good status. Very good confition was in Transecr I and II, whereas good condition on Transect III. Dominant lifeform of growth on Transect I and III was coral branching. The percentage cover of coral branching on Transect I was 59% and Transect III was 20%. Lifeform growth of coral branching found was dominated by coral genus Montipora and Psammocora. Genus Montipora on this area was spesies Montipora digitata. On the other hand, genus Psammocora found in the same location was spesies Psammocora contigua. Moreover, dominant lifeform of growth on Transect II was Coral Encrusting (28%). Physical chemical quality of sea-water in Pasir Putih consisted of temperature 27,5-29°C, dissolved oxigen 5,08-5,2 ppm, pH 7,03-7,15, salinity 30-31‰, current 0,08 m/s and clearness 16 m. These grades of physical chemical quality of sea-water was ideal to the growth of coral reef. Correlation of water quality parameter that has most siginificant effect (ρ = 0,01) to coral reef percent cover was temperature, dissolved oxygen and water depth.